Răspuns :
(3+√2)²-12supra√2=
3+√4-12supra√2=
√7-12supra√2=
-√5supra√2
3+√4-12supra√2=
√7-12supra√2=
-√5supra√2
[tex](3+ \sqrt{2})^{2} - \frac{12}{ \sqrt{2} }[/tex]
[tex]3^{2} +2*3* \sqrt{2}+ \sqrt{2}^{2} - \frac{12}{ \sqrt{2} }[/tex]
[tex]9+2*3* \sqrt{2}+2- \frac{12}{ \sqrt{2}}[/tex]
[tex]11+6* \sqrt{2} - \frac{12}{ \sqrt{2} }= \\ 11+6\sqrt{2} - \frac{12* \sqrt{2} }{2}[/tex] (am rationalizat cu √2)
[tex]11+ 6\sqrt{2} -6\sqrt{2}= 11 +0=11[/tex]
[tex]3^{2} +2*3* \sqrt{2}+ \sqrt{2}^{2} - \frac{12}{ \sqrt{2} }[/tex]
[tex]9+2*3* \sqrt{2}+2- \frac{12}{ \sqrt{2}}[/tex]
[tex]11+6* \sqrt{2} - \frac{12}{ \sqrt{2} }= \\ 11+6\sqrt{2} - \frac{12* \sqrt{2} }{2}[/tex] (am rationalizat cu √2)
[tex]11+ 6\sqrt{2} -6\sqrt{2}= 11 +0=11[/tex]